RNAi‐based targeted gene knockdown in the model oleaginous microalgae Nannochloropsis oceanica. (11th February 2017) - Wei, Li; Xin, Yi; Wang, Qintao; Yang, Juan; Hu, Hanhua; Xu, Jian
Summary: Microalgae are promising feedstock for renewable fuels such as biodiesel, yet development of industrial oleaginous strains has been hindered by the paucity and inefficiency of reverse genetics tools. Here we established an efficient RNAi‐based targeted gene‐knockdown method for Nannochloropsis spp., which are emerging model organisms for industrial microalgal oil production. The method achieved a 40–80% success rate in Nannochloropsis oceanica strain IMET1. When transcript level of one carbonic anhydrase ( CA ) was inhibited by 62–83% via RNAi, mutant cells exhibited photosynthetic oxygen evolution (POE) rates that were 68–100% higher than wild‐type (WT) at pH 6.0, equivalent to WT at pH 8.2, yet 39–45% lower than WT at pH 9.0. Moreover, the mutant POE rates were negatively correlated with the increase of culture pH, an exact opposite of WT. Thus, a dynamic carbon concentration mechanism (CCM) that is highly sensitive to pH homeostasis was revealed, where the CA inhibition likely partially abrogated the mechanism that normally deactivates CCM under a high level of dissolved CO2 . Extension of the method to another sequenced N. oceanica strain of CCMP 1779 demonstrated comparable performance. Finally, McrBC‐PCR followed by bisulfite sequencing revealed that the gene knockdown is mediated by the CG, CHG and CHH types of DNA methylation at the coding region of the targeted gene. The efficiency, robustness and general applicability of this reverse genetics approach suggested the possibility of large‐scale RNAi‐based gene function screening in industrial microalgae. Significance Statement: Microalgae are promising feedstocks for renewable fuels, yet the paucity and inefficiency of reverse genetics tools have hindered mechanistic understanding and development of superior industrial strains. Here we established an efficient RNAi‐based targeted gene‐knockdown method for Nannochloropsis oceanica, which will facilitate analysis of gene function.